2014
DOI: 10.1016/j.neuron.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Descending Control of Itch Transmission by the Serotonergic System via 5-HT1A-Facilitated GRP-GRPR Signaling

Abstract: SUMMARY Central serotonin (5-HT) modulates somatosensory transduction, but how it achieves sensory modality-specific modulation remains unclear. Here we report that enhancing serotonergic tone via administration of 5-hydroxytryptophan potentiates itch sensation, whereas mice lacking 5-HT or serotonergic neurons in the brainstem exhibit markedly reduced scratching behavior. Through pharmacological and behavioral screening, we identified 5-HT1A as a key receptor in facilitating gastrin-releasing peptide (GRP)-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
118
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 63 publications
(106 reference statements)
4
118
1
1
Order By: Relevance
“…Pharmacological and genetic ablation studies have shown that HTR1a, HTR1b, HTR2a, HTR2b and HTR3a mediate some forms of acute and inflammatory pain transmission (Abbott et al, 1996; Kayser et al, 2007; Lin et al, 2011; Nojima and Carstens, 2003; Van Steenwinckel et al, 2008; Zeitz et al, 2002). Pharmacological studies have also implicated peripheral HTR2a, HTR2b and HTR3 receptors, and central HTR1a receptors in itch (Bonnet et al, 2008; Imamachi et al, 2009; Kyriakides et al, 1999; Liu et al, 2013; Zhao et al, 2014), but to date there has been no genetic evidence for any 5-HT receptor in transducing serotonergic itch signals in primary afferent neurons. We have used genetic and pharmacological tools to show that HTR7 plays a selective role in acute serotonergic and atopic dermatitis itch, but not pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological and genetic ablation studies have shown that HTR1a, HTR1b, HTR2a, HTR2b and HTR3a mediate some forms of acute and inflammatory pain transmission (Abbott et al, 1996; Kayser et al, 2007; Lin et al, 2011; Nojima and Carstens, 2003; Van Steenwinckel et al, 2008; Zeitz et al, 2002). Pharmacological studies have also implicated peripheral HTR2a, HTR2b and HTR3 receptors, and central HTR1a receptors in itch (Bonnet et al, 2008; Imamachi et al, 2009; Kyriakides et al, 1999; Liu et al, 2013; Zhao et al, 2014), but to date there has been no genetic evidence for any 5-HT receptor in transducing serotonergic itch signals in primary afferent neurons. We have used genetic and pharmacological tools to show that HTR7 plays a selective role in acute serotonergic and atopic dermatitis itch, but not pain.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, recent research has suggested that the GRP-GRPR pathway is primarily engaged in transducing nonhistaminergic acute itch sensation and may play a relatively minor role in histaminergic itch. 46 Peripheral activation of dorsal horn neurons that express GRPR was also shown to be mediated through C-fibers and to involve glutamate release, although some Ad fiber signaling was also reported. 20 However, the location of GRP-immunoreactive neurons in neural circuits mediating itch remains controversial.…”
Section: Itch-specific Primary Afferent Fibersmentioning
confidence: 99%
“…Among monoamine neurotransmitters, serotonin, or 5-hydroxytryptamine (5-HT), is considered to play key and complex role in pain sensation25, and recently it was also demonstrated its crucial role in itch sensation26. To date, seven classes of 5-HT receptors (5-HT 1 -5-HT 7 ) have been identified and comprise at least 15 subtypes25.…”
mentioning
confidence: 99%
“…Except 5-HT 3 receptor as a ligand-gated cation channel, all other 5-HT receptors are G protein-coupled receptors (GPCRs)25. As 5-HT is not able to penetrate the blood-brain-barrier (BBB), peripheral and central 5-HT systems are considered to be separated compartments and employ distinct rate-limiting enzymes for 5-HT synthesis, such as tryptophan hydroxylase 1 ( Tph1 ) in the skin and tryptophan hydroxylase 1 ( Tph2 ) in the brain26. 5-HT in the skin released from mast cells, as a critical component of “inflammatory soup”, was identified as a potent inducer of pain or itch via activation distinct 5-HT receptors subtypes, such as 5-HT 2A , 5-HT 2B , 5-HT 2C , 5-HT 3 , 5-HT 4 , 5-HT 6 , and 5-HT 7 272829.…”
mentioning
confidence: 99%